The veil of participation : citizens and political parties in constitution-making processes / Alexander Hudson. - Hudson, Alexander (Comparative constitutional law and policy., 2021)
Public participation is a vital part of constitution-making processes around the world, but we know very little about the extent to which participation affects constitutional texts. In this book, Alexander Hudson offers a systematic measurement of the impact of public participation in three much-cited cases - Brazil, South Africa, and Iceland - and introduces a theory of party-mediated public participation. He argues that public participation has limited potential to affect the constitutional text but that the effectiveness of participation varies with the political context. Party strength is the key factor, as strong political parties are unlikely to incorporate public input, while weaker parties are comparatively more responsive to public input. This party-mediation thesis fundamentally challenges the contemporary consensus on the design of constitution-making processes and places new emphasis on the role of political parties.